2012
DOI: 10.1007/s11434-012-5461-z
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the kinase domain of human RNA-dependent protein kinase with K296R mutation reveals a face-to-face dimer

Abstract: RNA-dependent protein kinase (PKR) is crucial for the innate immune response, cell growth, proliferation, signal transduction and apoptosis. The activation process of PKR has been studied for many years and is still under debate. To obtain new insight into the mechanism of PKR activation, we solved the crystal structure of a latent mutant of the PKR kinase domain (PKR-KD) in the apo form at a resolution of 2.9 Å. The overall structure of PKR-KD is similar to previously reported structures. Structural analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…The association of RBM2 on the alternative face, at the C-lobe of the kinase domain, could also repress dimerization by impeding the formation of transitional states of PKR. Although PKR protomers associate in a back-to-back orientation in the active enzyme22, Li et al 51. identified that introducing a phosphor-mimetic mutated at the essential catalytic residue (T446D) in the kinase-dead molecule enabled them to isolate a dimeric molecule that adopted an alternative face-to-face orientation.…”
Section: Discussionmentioning
confidence: 99%
“…The association of RBM2 on the alternative face, at the C-lobe of the kinase domain, could also repress dimerization by impeding the formation of transitional states of PKR. Although PKR protomers associate in a back-to-back orientation in the active enzyme22, Li et al 51. identified that introducing a phosphor-mimetic mutated at the essential catalytic residue (T446D) in the kinase-dead molecule enabled them to isolate a dimeric molecule that adopted an alternative face-to-face orientation.…”
Section: Discussionmentioning
confidence: 99%
“…Although the structure of inactive, monomeric PKR is not available, the structure of the active, dimeric PKR kinase domain suggested that the dimerization of the N-terminal lobe of the kinase domain likely induces conformational changes in the αC helix and the activation segments in a manner similar to other wellcharacterized kinases (69, 80) ( Figure 2b). The structure also showed how the autophosphorylation of Thr446 in the activation segment further helps stabilize the active site conformation (80,81) (Figure 2b). Altogether, these observations support the model where dsRNA binding brings two or more PKR molecules in close proximity to allow dimerization of the kinase domain ( Figure 2b).…”
Section: Protein Kinase Rmentioning
confidence: 95%
“…The X-ray structure of a kinase-dead K296R PKR mutant was essentially identical to the wild-type activated structure, except for the disordered activation and P + 1 loops due to unphosphorylated T446 ( Fig. 1D; Li et al 2012). Since high concentrations of PKR can induce dimerization and activation (Lemaire et al 2005), this mutant structure likely represents an activated state prior to autophosphorylation instead of an authentic inactive state.…”
Section: Effector Kinase Domainmentioning
confidence: 83%